Their own frontier : women intellectuals re-visioning the American West - Leckie, Shirley A., 1937-; Parezo, Nancy J. (Women in the West., 2008)
The ten women intellectuals showcased in this volume were pioneers in the writing of Indian-centered history, ethnology, and folklore that incorporated the insights, voices, and perspectives of American Indians. These authors not only produced significant works that are still useful to modern-day scholars; they also pioneered research methods and theoretical concepts that helped lay the foundation for the new scholarship on western history, American Indian studies, and ethnohistory. Noted scholars have provided individual biographies describing the struggles and contributions these foremothers.